PENGARUH AROMATERAPI MAWAR TERHADAP KUALITAS TIDUR LANSIA DI PANTI SOSIAL TRESNA WERDHA UNIT BUDI LUHUR KASONGAN BANTUL YOGYAKARTA - Foerwanto, Foerwanto; Nofiyanto, Muhamat; Prabowo, Tri (Media Ilmu Kesehatan, 2016)
Background:Sleep is a very fundamental need for every individual, especially for elderly people in social institutions. Poor quality of sleep in the elderly may lead to several disturbances, such as vulnerability to diseases,forgetfulness, psychomotor disorders, disorientation and difficulty to make decision. Some intervention may include pharmacological and non-pharmacological therapy. One of non-pharmacology therapies that isused to increase sleep qualityis rose aromatherapy. Objective: To determine the effect of rose aromatherapy on the quality of sleep in elderly at PSTW Budi Luhur Kasongan Bantul, Yogyakarta. Method: This study was a quasi-experiment research,with one group pretest-posttest design. Samples were taken with simple random sampling technique, involving 24 respondents. Each respondent was given rose aromatherapy for 5 minutes for 5 consecutive days. Result:Statistical analysis with marginal-homogeneity test showed p-value of 0,000 (p value<0,05).It suggested that there was a significant effect ofrose aromatherapy on the quality of sleep in elderly at Social Institution of Tresna Werdha Budi Luhur Kasongan Bantul, Yogyakarta. Conclusion:Roses aroma therapy has effect in improving sleep quality in the elderly at Social Institution of TresnaWerdha Budi LuhurKasonganBantul, Yogyakarta. Keywords: Elderly, PSTW, Sleep quality, Aromatherapy, Rose.